Dependency and self-criticism in treatments for depression - Chui, Harold; Zilcha-Mano, Sigal; Dinger, Ulrike; Barrett, Marna S.; Barber, Jacques P. (Journal of counseling psychology, 2016)
Dependency and self-criticism are vulnerability factors for depression. How these personality factors change with treatment for depression, and how they relate to symptom change across different types of treatment require further research. In addition, cultural differences that interact with the dependency/self-criticism-depression relation remain under-investigated. One hundred and forty-nine adults with major depression were randomly assigned to receive active medication (MED; n = 50), supportive-expressive therapy (SET; n = 49), or placebo pill (PBO; n = 50). Participants completed the Depressive Experiences Questionnaire (DEQ; ) before and after treatment, and were administered the Hamilton Rating Scale for Depression () throughout the course of treatment. Self-criticism as measured on the DEQ decreased with treatment similarly across conditions. DEQ Dependency decreased in MED but remained unchanged in SET and PBO. Higher initial dependency, but not higher initial self-criticism, predicted poor treatment response across conditions. Greater reduction in self-criticism was associated with greater reduction in depressive symptoms, but the effect was weaker for racial minorities (vs. White). Increase in connectedness, an adaptive form of dependency, was associated with symptom improvement in SET but not MED. Hence, different pathways of change seem to be implicated in the treatment of depression depending on culture and type of intervention. Implications for future research are discussed.
Gesehen am 04.05.2020